Molecular consequences of cystic fibrosis transmembrane regulator (CFTR) gene mutations in the exocrine pancreas. Issue 8 (15th July 2003) - Ahmed, N; Corey, M; Forstner, G; Zielenski, J; Tsui, L-C; Ellis, L; Tullis, E; Durie, P
Abstract : Background and aims: We tested the hypothesis that the actual or predicted consequences of mutations in the cystic fibrosis transmembrane regulator gene correlate with the pancreatic phenotype and with measures of quantitative exocrine pancreatic function. Methods: We assessed 742 patients with cystic fibrosis for whom genotype and clinical data were available. At diagnosis, 610 were pancreatic insufficient, 110 were pancreatic sufficient, and 22 pancreatic sufficient patients progressed to pancreatic insufficiency after diagnosis. Results: We identified mutations on both alleles in 633 patients (85.3%), on one allele in 95 (12.8%), and on neither allele in 14 (1.9%). Seventy six different mutations were identified. The most common mutation was ΔF508 (71.3%) followed by G551D (2.9%), G542X (2.3%), 621+1G→T (1.2%), and W1282X (1.2%). Patients were categorized into five classes according to the predicted functional consequences of each mutation. Over 95% of patients with severe class I, II, and III mutations were pancreatic insufficient or progressed to pancreatic insufficiency. In contrast, patients with mild class IV and V mutations were consistently pancreatic sufficient. In all but four cases each genotype correlated exclusively with the pancreatic phenotype. Quantitative data of acinar and ductular secretion were available in 93 patients. Patients with mutations belonging to classes I, II, and III had greatly reduced acinar and ductular function compared with those with class IV or V mutations. Conclusion: The predicted or known functional consequences of specific mutant alleles correlate with the severity of pancreatic disease in cystic fibrosis.